The organization and impacts of clinical research delivery workforce redeployment during the COVID-19 pandemic: a qualitative case study of one research-intensive acute hospital trust - Rachel Faulkner-Gurstein; David Wyatt; Hannah Cowan; Naomi Hare; Clair Harris; Charles Wolfe (Health Research Policy and Systems, 2022)
Abstract Background COVID-19 has tested healthcare and research systems around the world, forcing the large-scale reorganization of hospitals, research infrastructure and resources. The United Kingdom has been singled out for the speed and scale of its research response. The efficiency of the United Kingdom’s research mobilization was in large part predicated on the pre-existing embeddedness of the clinical research system within the National Health Service (NHS), a public, free-at-point-of-delivery healthcare system. In this paper we discuss the redeployment of the clinical research workforce to support the pandemic clinical services, detailing the process of organizing this redeployment, as well as the impacts redeployment has had on both staff and research delivery at one research-intensive acute NHS trust in London. Methods A social science case study of one large research-active NHS trust drawing on data from an online questionnaire; participant observation of key research planning meetings; semi-structured interviews with staff involved in research; and document analysis of emails and official national and trust communications. Results We found that at our case-study hospital trust, the research workforce was a resource that was effectively redeployed as part of the pandemic response. Research delivery workers were redeployed to clinical roles, to COVID-related research and to work maintaining the research system during the redeployment itself. Redeployed research workers faced some difficulties with technology and communication, but many had a positive experience and saw the redeployment as a significant and valuable moment in their career. Conclusions This study explicates the role of the research delivery workforce for the United Kingdom’s COVID response. Redeployed research workers facilitated the emergency response by delivering significant amounts of patient care. The public also benefited from having a well-developed research infrastructure in place that was able to flexibly respond to a novel virus. Many research workers feel that the NHS should provide more support for this distinctive workforce.